Gouverner la vie privée: l'encadrement inégalitaire des séparations conjugales en France et au Québec - Biland, Émilie (ENS Éditions, 2019)
"L'implication de l'État dans la vie privée pose problème : les individus ont davantage de droits que par le passé, mais certains de leurs comportements, jugés problématiques pour la collectivité, justifient un interventionnisme renouvelé, dans lequel acteurs privés et mécanismes de marché occupent une place croissante. En tension entre libéralisme et normalisation, cette action publique participe aux recompositions des rapports sociaux, entre les classes sociales, entre les genres, ainsi qu'entre la population majoritaire et les personnes racisées. Objet de vifs débats et de réformes récurrentes, la régulation par le droit des séparations conjugales est un observatoire précieux de ces recompositions, ici analysées à partir de trois enquêtes collectives, qualitatives et quantitatives, menées des deux côtés de l'Atlantique. En France comme au Québec, l'accès aux procédures, les interactions avec les professionnel.les et l'encadrement des modes de vie sont les trois dimensions constitutives du gouvernement de la vie privée. Cependant, chacun des contextes n'articule pas de la même manière inégalités de classe et inégalités de genre. En scrutant la production institutionnelle des inégalités privées, cet ouvrage invite à imaginer des voies alternatives, dans la sphère privée comme dans la sphère publique, pour que la politique des droits tienne ses promesses émancipatrices."
Section: 257 pages : tableaux ; 23 cm.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; droit des femmes*; droits des femmes*; europe; famille; france; hétérosexualité; inégalités; mariage; maternité; parentalité; patriarcat; premier cycle; privilèges; périodes historiques; québec; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexualité; soc2262; soc2264; sociologie; systèmes d'oppressions; séparation; thématiques

Delivered by women, led by men: A gender and equity analysis of the global health and social workforce - World Health Organization (World Health Organization, 2019)
Demographic changes and rising health care demands are projected to drive the creation of 40 million new jobs by 2030 in the global health and social sector. In parallel, there is an estimated shortfall of 18 million health workers, primarily in low- and middle-income countries, required to achieve the Sustainable Development Goals (SDGs) and universal health coverage. The global mismatch between health worker supply and demand is both a cause for concern and a potential opportunity. Since women account for 70% of the health and social care workforce, gaps in health worker supply will not be closed without addressing the gender dynamics of the health and social workforce. The female health and social care workers who deliver the majority of care in all settings face barriers at work not faced by their male colleagues. This not only undermines their own well-being and livelihoods, it also constrains progress on gender equality and negatively impacts health systems and the delivery of quality care. In November 2017, the World Health Organization (WHO) established the Gender Equity Hub (GEH), co-chaired by WHO and Women in Global Health under the umbrella of the Global Health Workforce Network. The GEH brings together key stakeholders to strengthen gender-transformative policy guidance and implementation capacity for overcoming gender biases and inequalities in the global health and social workforce, in support of the implementation of the Global Strategy on Human Resources for Health: Workforce 2030, and the Working for Health five-year action plan (2017–2021) of WHO, the International Labour Organization (ILO) and the Organisation for Economic Co-operation and Development (OECD). In 2018, the GEH identified and reviewed over 170 studies in a literature review of gender and equity in the global health workforce, with a focus on four themes: occupational segregation; decent work free from bias, discrimination and harassment, including sexual harassment; gender pay gap; and gender parity in leadership. This report will inform the next phase of the work of the Global Health Workforce Network GEH, which seeks to use these research findings to advocate gender-transformative policy and action.
https://apps.who.int/iris/handle/10665/311322
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discours dominant; droits des femmes*; inégalités; inégalités salariales; projet charge mentale; périodes historiques; rapports sociaux de sexe; systèmes d'oppressions; thématiques; travail; travailleureuses de la santé

Conférence: «Droit et féminisme - Rencontre entre deux champs» - Institut de recherches et d'études féministes; Réseau Québécois en études féministes (2018)
Avec Rachel Chagnon, membre de l'Institut de recherches et d'études féministes et professeure au Département des sciences juridiques.
Keywords: amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; europe; féminisme décolonial; histoire du féminisme; intersectionnalité; inégalités; militance; mouvements des femmes*; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique et droit; sciences humaines; sciences juridiques; sociologie; système colonial; systèmes d'oppressions; thématiques

Undivided rights: Women of color organizing for reproductive justice - Silliman, Jael; Fried, Marlene Gerber; Ross, Loretta; Gutiérrez, Elena (Haymarket Books, 2016)
Undivided Rights captures the evolving and largely unknown activist history of women of color organizing for reproductive justice—on their own behalf.Undivided Rights presents a textured understanding of the reproductive rights movement by placing the experiences, priorities, and activism of women of color in the foreground. Using historical research, original organizational case studies, and personal interviews, the authors illuminate how women of color have led the fight to control their own bodies and reproductive destinies. Undivided Rights shows how women of color—-starting within their own Latina, African American, Native American, and Asian American communities—have resisted coercion of their reproductive abilities. Projected against the backdrop of the mainstream pro-choice movement and radical right agendas, these dynamic case studies feature the groundbreaking work being done by health and reproductive rights organizations led by women-of-color.The book details how and why these women have defined and implemented expansive reproductive health agendas that reject legalistic remedies and seek instead to address the wider needs of their communities. It stresses the urgency for innovative strategies that push beyond the traditional base and goals of the mainstream pro-choice movement—strategies that are broadly inclusive while being specific, strategies that speak to all women by speaking to each woman. While the authors raise tough questions about inclusion, identity politics, and the future of women’s organizing, they also offer a way out of the limiting focus on "choice."Undivided Rights articulates a holistic vision for reproductive freedom. It refuses to allow our human rights to be divvied up and parceled out into isolated boxes that people are then forced to pick and choose among.
Keywords: afro-féminisme; amériques; approches et analyses; discours dominant; droits des femmes*; histoire et politique; intersectionnalité; inégalités; justice reproductive; militance; régions géographiques; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis

« Gender Equality and Economic Inequality: Impact on Marriage » dans Gender and couple relationships - Coontz, Stephanie (Gender and couple relationships, 2016)
Changes in aggregate marriage rates and in the internal dynamics of individual marriages should be understood as the outcome of two powerful but very different trends in gender and class relations. One trend is the uneven but undeniably dramatic progress toward equality in personal life and cultural values, which has led to widespread repudiation of centuries-old gender hierarchies. The other trend is an equally powerful movement toward growing inequality, insecurity, and unpredictability in economic life, which has resulted in substantial losses for the most historically vulnerable and least-educated sections of the workforce. The ongoing gender revolution interacts with widening economic inequality in complex ways, increasing the benefits of marriage for individuals with higher earning power while increasing the risks of marriage for low-income individuals, especially women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; care; cours; discipline; discours dominant; droits des femmes*; famille; inégalités; mariage; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; soc2262; sociologie; systèmes d'oppressions; thématiques; états-unis

Entrevue de Maria Nengeh Mensah sur les ondes du Canal Savoir - Mensah, Maria Nengeh (2013)
Maria Nengeh Mensah, professeure à l'École de travail social de l'UQAM et coauteure de l’ouvrage «Luttes XXX : Inspirations du mouvement des travailleuses du sexe», explique les revendications de ces travailleuses qui prolongent le sens des luttes pour les droits des femmes.
Keywords: approches et analyses; discipline; discours dominant; droits des femmes*; histoire et politique; militance; ressource en ligne; santé; sciences humaines; sexualité; systèmes d'oppressions; thématiques; travail du sexe-prostitution; travail social; témoignage

Les insoumises : la révolution féministe - Bard, Christine (Le Monde, 2013)
Se rebeller contre la condition faite aux femmes, voilà qui pourrait servir de définition au féminisme. D'Olympe de Gouges à Chahla Chafiq, d'Hubertine Auclert à Virginie Despentes en passant par Louise Michel, Simone de Beauvoir, Gisèle Halimi, le féminisme délivre un message universel et continue de nous interpeller, parce qu'il porte la voix d'insoumises, de femmes qui veulent choisir leur vie, pour qui la biologie ou les rôles sexués ne doivent pas être un destin. Il dénonce les inégalités entre les sexes dans la sphère publique - répartition du pouvoir et des richesses matérielles et symboliques - et prend la défense de la liberté des femmes : respect de l'intégrité physique, maîtrise de la fécondité, droit de choisir sa sexualité. Articles de presse, manifestes, romans, poésie, Mémoires : les insoumises d'hier et d'aujourd'hui (r)éveillent les consciences endormies.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; droits des femmes*; fem1000; fem7000; histoire; lit3220; militance; mouvements féministes; premier cycle; sciences humaines; sex3383; systèmes d'oppressions; thématiques

Luttes XXX : inspirations du mouvement des travailleuses du sexe - Mensah, Maria Nengeh; Toupin, Louise; Thiboutot, Claire (Les éditions du remue-ménage, 2011)
Depuis 1973, des travailleuses et travailleurs du sexe aux quatre coins de la planète se regroupent et se mobilisent. Qui sont ces personnes, comment s’organisent-elles et pourquoi revendiquent-elles la décriminalisation de leur travail? Qu’ont-elles à dire à propos du syndicalisme, du féminisme, de la lutte contre le sida, de la violence ou des phénomènes migratoires? Tout en situant le mouvement des travailleuses du sexe dans son contexte historique et international, cette anthologie unique propose une sélection de documents inédits ou traduits en français pour la première fois. Luttes XXX nous invite à la rencontre d’un mouvement social méconnu. Ici, les voix des travailleuses et travailleurs du sexe, longtemps réduites au silence, s’élèvent, réclament justice.
Keywords: anthologie; approches et analyses; cours; discours dominant; droits des femmes*; fem1000; international; inégalités; justice sociale; mouvements sociaux; premier cycle; santé; systèmes d'oppressions; thématiques; travail; travail du sexe; témoignage

Beyond subordination vs. resistance: An intersectional approach to the agency of veiled muslim women - Bilge, Sirma (Journal of Intercultural Studies, 2010)
Engaging with a figure that came to operate as a powerful cultural signifier of otherness in debates over migrant/Muslim integration across the West, the ‘veiled woman’; the paper questions the idea of agency that inheres in the contemporary feminist discourses on Muslim veil. After showing the shortcomings and adverse effects of two dominant readings of the Muslim veil, as a symbol of women's subordination to men, or as an act of resistance to Western hegemony, it explores an alternative avenue drawing on both the poststructuralist critique of the humanist subject and feminist intersectional theorising to answer the question of what kind of conception of agency can help us to think about the agency of the veiled woman without binding a priori the meaning of her veiling to the teleology of emancipation, whether feminist or anti-imperialist.
Keywords: agentivité; approches et analyses; discipline; discours dominant; droits des femmes*; femmes* musulmanes; intersectionnalité; post-structuralisme; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions; thématiques; voiles islamiques

Sous les yeux de l’Occident : recherches féministes et discours coloniaux - Mohanty, Chandra Talpade (Genre, postcolonialisme et diversité de mouvements de femmes, 2010)
Note de l’éditeur Traduit de l’anglais. Texte original: Under Western eyes : Feminist scholarship and colonial discourses. In Feminism without borders : Decolonizing theory, practicing solidarity. 17-42. Durham : Duke University Press. 2003. Tous droits réservés. Reproduit avec l’aimable autorisation de l’éditeur. Parution originale 1986.
Keywords: EDI; afro-féminisme; approches et analyses; cours; discipline; discours dominant; droits des femmes*; ethnocentrisme; féminisme africain; féminisme autochtone; féminisme du sud; féminisme décolonial; féminisme transnational; histoire et politique; injustices épistémiques; inégalités; justice sociale; militance; patriarcat; phi4336; philosophie politique; pol4212; pratiques féministes; premier cycle; privilèges; racisme; sciences humaines; sociologie; sujet du féminisme; système colonial; systèmes d'oppressions; thématiques; théorie féministe; violences